GLYCATED LOW-DENSITY LIPOPROTEIN IN DIABETIC AND NON-DIABETIC PATIENTS - AL-ANI, OMAR ABDULWAHID; AL-BAZZAZ, ABDURRAHMAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The importance of measuring the blood level of modified low-density lipoprotein (LDL) molecules is an effective method of identifying people at risk of coronary atherosclerosis; this is because, in the early stages of atherosclerosis, lipolysis and oxidative modification have a role in promoting the uptake of these lipids through macrophages; therefore, this research aims to measure the level of glycated LDL (Gly-LDL) in the blood and its association with metabolic parameters of diabetic patients (diabetes mellitus) and non-diabetic (hyperlipidemia). Methods: At a University Diabetes Center in Riyadh, we using routine automatic analysis methods, fasting serum samples were analyzed for 31 patients with Type-2 diabetes and 31 non-diabetic patients for LDL, high-density lipoprotein (HDL), total cholesterol, glycated hemoglobin, glucose, and triglycerides (TG), and using enzyme-linked immunosorbent assay to analyze Gly-LDL for the same sample. Results: The level of serum Gly-LDL in non-diabetic was higher than in diabetic patients (p=0.037). Gly-LDL level correlated significantly with LDL in the diabetic group (p=0.035) and was insignificant with other parameters; moreover, it is significantly correlated with HDL (p=0.048), TG (p=0.035), and very LDL (p=0.03) in the non-diabetic group and insignificant with other parameters. Conclusion: Measuring rates of Gly-LDL can be used in the early detection of cardiovascular disease, especially in people with diabetes, as they are more susceptible to modified and oxidized LDL.